Philanthropy: A Customary Practice to Meet Donor Expectation. Lesson from Islamic NPOs in Indonesia - Rejosumarto, Muji Astuti; Bulut, Mehmet (European Scientific Journal, ESJ, 2024)
Philanthropy is a form of altruism that involves how private initiatives enhance the public good. Throughout history, benevolence has appeared in numerous shapes and objectives, representing the economic and political framework, righteous systems, and enlightening different motivations. Non-profit organizations (NPOs) in Indonesia have undergone tremendous transformations, evolving more modern and professional. They determine market segments and manage donor acquaintances, formulate fundraising strategies, and construct appropriate, impactful, and beneficial programs with the concourse of the organization’s system and human capital. Aside from that, Islamic NPOs appear more strategic, preserve a clear vision and mission, establish an organizational structure and qualified leaders, design long-term, medium-term, and short-term activity plans and budgets, appoint program supervisors, and assess the effectiveness and efficiency of their schedules. The purpose of this research is to comprehend the broad issues confronting Islamic charity in Indonesia as it evolves towards a strategic and lucrative institution. This study adopts qualitative methodologies to discover comprehensive explanations for the occurrences under consideration. In-depth semi-structured interviews with an array of practitioners and academics were employed to gather data. This study indicates that there is a great deal to be performed to improve the capabilities of Islamic NPOs in terms of good governance, system strengthening, cultural internalization, public openness, and accountability as an effective intermediary organization to meet donor expectations. With the role of enabling the transformation of beneficiaries to be more prosperous and avoid poverty or weakness, Islamic NPOs must accelerate capacity building by enhancing each aspect of the organization.